A Test of Conspicuous Consumption: Visibility and Income Elasticities - Heffetz, Ori (The Review of Economics and Statistics, 2011)
This paper shows that, consistent with a signaling-by-consuming model à la Veblen, income elasticities can be predicted from the visibility of consumer expenditures. We outline a stylized conspicuous consumption model where income elasticity is endogenously predicted to be higher if a good is visible and lower if it is not. We then develop a survey-based measure of expenditure visibility, ranking different expenditures by how noticeable they are to others. Finally, we show that our visibility measure predicts up to one-third of the observed variation in elasticities across consumption categories in U.S. data.